2023
DOI: 10.1021/acsomega.3c03530
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Remarkably Potential Multitarget-Directed N-Alkylated-2-(substituted phenyl)-1H-benzimidazole Derivatives as Antiproliferative, Antifungal, and Antibacterial Agents

Abstract: Improving lipophilicity for drugs to penetrate the lipid membrane and decreasing bacterial and fungal coinfections for patients with cancer pose challenges in the drug development process. Here, a series of new N-alkylated-2-(substituted phenyl)-1H-benzimidazole derivatives were synthesized and characterized by 1 H and 13 C NMR, FTIR, and HRMS spectrum analyses to address these difficulties. All the compounds were evaluated for their antiproliferative, antibacterial, and antifungal activities. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Most of the compounds that have shown antibacterial activity against E. coli are the 5-substituted benzimidazoles 3q, 3r, 3v, and 3w. The low activity of benzimidazoles against Gram-negative bacteria was also observed in other studies [26,30]. This is probably due to the structure of the cell wall of this group of bacteria, which contains an outer membrane.…”
Section: Antimicrobial Activitysupporting
confidence: 70%
See 2 more Smart Citations
“…Most of the compounds that have shown antibacterial activity against E. coli are the 5-substituted benzimidazoles 3q, 3r, 3v, and 3w. The low activity of benzimidazoles against Gram-negative bacteria was also observed in other studies [26,30]. This is probably due to the structure of the cell wall of this group of bacteria, which contains an outer membrane.…”
Section: Antimicrobial Activitysupporting
confidence: 70%
“…In continuation of our previous work on the development of an effective strategy for the synthesis of antibacterial compounds [25], we have become interested in finding the chemoselective pathway of 2-(1H-indol-3-yl)-1H-benzo[d]imidazole derivatives [26]. We have previously shown that the condensation of anthranilamides with aldehydes on heating in N,N-dimethylacetamide (DMAC) in the presence of sodium metabisulfite leads to the formation of antibacterial 2-(1H-indol-3-yl)quinazolin-4(3H)-ones and their analogs.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi stand out as exceptional creators of a broad spectrum of natural products, contributing to biodiversity and offering a treasure trove of compounds imbued with a wide range of biological functions [1,2]. Notably, mushrooms, a type of fungi [3], assume a pivotal role in traditional agriculture, cuisine, and medicinal practices [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Benzimidazole is a privileged structural motif frequently found in marketed drug molecules, such as Omeprazole, Albendazole, Liarozole, Telmisartan, and Mibefradil . This heterocyclic pharmacophore exhibits diverse biological properties, including anti-inflammatory, anticancer, antimicrobial, antiviral, antifungal, and so on . Particularly, tricyclic and 1,2-disubstituted chiral benzimidazole derivatives demonstrate a broad spectrum of pharmaceutical, biological activities (Figure A) .…”
mentioning
confidence: 99%